Inorganic phosphorus fractions and sorption capacity of sediments correlated with physicochemical parameters of water in Langat River, Selangor Malaysia - Jega, Bilyaminu Garba; Mustafa, Muskhazli; Rajaram, Micheal Charles; Abd Aziz, Nor Azwady; Wan Solahudin, Wan Mohd Syazwan; Hashim, Noor Haza Fazlin; Mohd Fazli, Bashirah (Universiti Putra Malaysia Press, 2025)
This study investigates the physicochemical parameters of water, their association with inorganic phosphate fractions, and the sorption capacity of sediments. Water and sediment samples were collected from upstream, midstream, and downstream sections between November 2022 and June 2023. The water samples were analysed according to the American Public Health Association (APHA) guidelines for physicochemical parameters. Inorganic phosphate fractions in the sediments were quantified using the molybdenum blue colourimetric method. Sediment phosphate sorption capacity was assessed by measuring the resulting filtrate and applying regression correlation and Langmuir isotherm models to determine the relationships among the sediment samples. Sediment analysis of inorganic phosphorous fractions revealed varying percentages of Ca-P (32.6%), Rs-P (38.3%), and Fe-P (48.4%) dominating the upstream, midstream, and downstream sections, respectively. Sediment phosphate adsorption varied between sections (upstream: 4.00 to 18.21 mg/g vs. midstream: 4.36 to 21.10 mg/g vs downstream: 4.00 to 12.98 mg/g), with no significant differences between streams at specific phosphate concentrations. However, all the sections displayed a saturation point of approximately 20–25 mg/l. The Langmuir isotherm parameters accurately described P adsorption onto Langat River sediments, as indicated by the moderately high R2 values for Qmax and RL. The downstream section of the Langat River had elevated levels of EC, COD and SRP parameters and Ex-P, Al-P, Fe-P, and Ca-P fractions, except for the Rs-P fraction that dominated the midstream section, indicating collective effects of anthropogenic activities. Therefore, strict regulations to improve wastewater treatment and promote sustainable wastewater management are essential for reducing inorganic phosphorus pollution in the Langat River and protecting water quality.